2015
DOI: 10.1186/s13054-015-0995-5
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary ultrasound and pulse oximetry versus chest radiography and arterial blood gas analysis for the diagnosis of acute respiratory distress syndrome: a pilot study

Abstract: IntroductionIn low-resource settings it is not always possible to acquire the information required to diagnose acute respiratory distress syndrome (ARDS). Ultrasound and pulse oximetry, however, may be available in these settings. This study was designed to test whether pulmonary ultrasound and pulse oximetry could be used in place of traditional radiographic and oxygenation evaluation for ARDS.MethodsThis study was a prospective, single-center study in the ICU of Harborview Medical Center, a referral hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 29 publications
1
47
0
3
Order By: Relevance
“…The study of these patterns shows very high sensitivity in cases of interstitial and alveolar-interstitial lung diseases, which have a peripheral distribution. Numerous studies on acute respiratory distress syndrome (ARDS) 6 confirm this. Other studies related to the 2009 pandemic influenza A (H1N1) epidemic 7 confirm these hypotheses even in a virally infectious setting.…”
Section: Is There a Role For Lung Ultrasound During The Covid-19 Pandmentioning
confidence: 90%
“…The study of these patterns shows very high sensitivity in cases of interstitial and alveolar-interstitial lung diseases, which have a peripheral distribution. Numerous studies on acute respiratory distress syndrome (ARDS) 6 confirm this. Other studies related to the 2009 pandemic influenza A (H1N1) epidemic 7 confirm these hypotheses even in a virally infectious setting.…”
Section: Is There a Role For Lung Ultrasound During The Covid-19 Pandmentioning
confidence: 90%
“…Apart from a small pilot study [ 11 ] and a recent evaluation of the Kigali Modification [ 12 ], the use of chest radiography versus the use of lung ultrasound for the identification of ARDS has not been systematically studied. It is also unclear how the choice of imaging would affect ARDS identification.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that venous PCO2 cannot be used to predict arterial PCO2 by applying a 'correction factor. ' Another investigation reported that the VBG might be useful in determining whether venous blood has a low amount of CO2 and high O2 to exclude hypercapnia and hypoxia [20]. Likewise, the systematic review of estimates of differences between VBG and ABG was subject to a high degree of heterogeneity, which might lead to a further bias.…”
Section: Discussionmentioning
confidence: 99%